PENINGKATAN KEMAMPUAN KEPALA SEKOLAH DALAM MENYUSUN PROGRAM SUPERVISI PENDIDIKAN MELALUI MUSYAWARAH KERJA KEPALA SEKOLAH (MKKS) BERBASIS PENDAMPINGAN DI SEKOLAH BINAAN - Samaun Samaun (JURNAL MANAJEMEN PENDIDIKAN, 2018)
Abstract Based on the results of the observations that researchers have done on the principal at the school in SMKN 1 Talamau, SMKN 1 Ranah Pasisie, found that the ability of the principal in preparing the program of supervision of education is still low. The purpose of this study is to describe and obtain information about the efforts of the principal's ability in preparing the program of supervision of education through the Consultative Working School Principal MKKS-based mentoring in the School. This study is a school action research. The research procedures in this study include planning, action, obeservation and reflection. This study consists of two cycles with four meetings. The subjects consist of 2 principals of Sekolah Binaan. Research data was collected using obeservation sheets. Data were analyzed using percentages. The results show that MKKS based mentoring can improve the ability of headmaster in preparing the program of supervision of education in Sekolah Binaan. This is evidenced by the increase in the ability of the principal in preparing the education supervision program from cycle I to cycle II. The average ability of headmaster in preparing the education supervision program in cycle I is 73.17 with enough category and in cycle II is 84.29 with good category. Keywords: Principal Ability, Education Supervision Program, MKKS